Application of the computing environment maple to the calculation of the dynamics of the electromagnets in the complicated systems of forced control - Baida, Evgeniy Ivanovich; Clemens, M.; Klymenko, Boris Vladimirovich; Korol, Elena Gennadyevna; Pustovoitov, P. Ye. (Національний технічний університет "Харківський політехнічний інститут", 2019)
The authors propose a technique for calculating the dynamics of electromagnets operating in complex forced systems. Such forced electromagnets are widely used in electromechanical switching devices, in particular in vacuum contactors, to reduce their size, energy consumption and to increase speed, which indicates the relevance of this topic. A mathematical model of the dynamics of a forced electromagnetic system, which takes into account the peculiarities of behavior in transients of its individual elements – the mechanical system, the magnetic and electrical circuits, taking into account the interaction of the electromagnet with a control device when the apparatus is activated, contains certain signs of scientific novelty and is the purpose of the paper. The technique of calculating the dynamics of forced electromagnets uses the computing environment Maple. The calculation is based on a mathematical model, which is a system of nonlinear differentialequations of the magnetic and electric circuits, supplemented by the equations of motion of the elements of a mechanical system. The use of the computing environment Maple, applied here to automatically perform the mathematical transformations, allowsavoiding the complicated processes of choosing the numerical integration method, programming of complex and cumbersome equations and numerical integration procedures, to obtain results of calculations in convenient tabular and/or graphic form. This specifically indicates the practical significanceof this work. The results of the comparison of calculations with previously published experimental data presented in the paper indicate the high efficiencyof the proposed models and techniques.

Розглядається запропонована авторами методика розрахунку динаміки електромагнітів, що працюють у складних форсованих системах. Подібні форсовані електромагніти широко застосовуються в електромеханічних комутаційних апаратах, зокрема у вакуумних контакторах, для зменшення їх розмірів, споживання енергії та для підвищення швидкодії, що свідчить про актуальність даної теми. Математична модель динаміки форсованої електромагнітної системи, що враховує особливості поведінки у нестаціонарних процесах її окремих елементів – механічної системи, магнітного та електричного кіл з урахуванням взаємодії електромагніта з пристроєм керування під час спрацьовування апарата, містить певні ознаки наукової новизни і є метою статті. Методика розрахунку динаміки форсованих електромагнітів застосовує математичний пакет Maple. В основу розрахунку покладено математичну модель, яка представляє собою систему нелінійних диференційних рівнянь магнітного і електричного кіл, доповнених рівняннями руху елементів механічної системи. Застосування пакетуMaple, який багато в чому бере на себе складнощі математичного опису різних процесів, автоматично здійснюючи дуже складні і громіздкі математичні перетворення, дозволяє, уникаючи складних процесів вибору способу чисельного інтегрування, програмування складних й громіздких рівнянь та процедур їх чисельного інтегрування, отримувати результати розрахунків у зручній табличній та/або графічній формі, що свідчить про практичну значущість даної роботи. Наведені у статті результати зіставлення розрахунків з опублікованими раніше експериментальними даними, свідчать про високу ефективність запропонованих моделей та методик
Keywords: switching devices; vacuum contactors; computing environment Maple; комутаційні апарати; вакуумні контактори; математичний пакет Maplе